2018
DOI: 10.1186/s13071-018-2832-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling of Aedes mosquito vectors of chikungunya virus in southeastern Senegal

Abstract: BackgroundChikungunya virus (CHIKV) originated in a sylvatic cycle of transmission between non-human animal hosts and vector mosquitoes in the forests of Africa. Subsequently the virus jumped out of this ancestral cycle into a human-endemic transmission cycle vectored by anthropophilic mosquitoes. Sylvatic CHIKV cycles persist in Africa and continue to spill over into humans, creating the potential for new CHIKV strains to enter human-endemic transmission. To mitigate such spillover, it is first necessary to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 90 publications
2
28
1
1
Order By: Relevance
“…The CHIKV was identified in Senegal in the 1960s [16,17], with defined outbreaks occurring in 2009, 2010, and 2015, and a known sylvatic cycle with infected monkeys identified in multiple studies [18,19,20,21]. Recent studies have confirmed current CHIKV presence in Senegal both by detection of active viremia and serological evidence [19,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…The CHIKV was identified in Senegal in the 1960s [16,17], with defined outbreaks occurring in 2009, 2010, and 2015, and a known sylvatic cycle with infected monkeys identified in multiple studies [18,19,20,21]. Recent studies have confirmed current CHIKV presence in Senegal both by detection of active viremia and serological evidence [19,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies modeling the distribution of vectors commonly use a 1 km spatial resolution because climate layers are only available at this coarse resolution [65,66,[75][76][77]. Because climate variables are often the most important predictors for SDMs of disease vectors, these data should be very detailed [35,65,66,75].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies modeling the distribution of vectors commonly use a 1 km spatial resolution because climate layers are only available at this coarse resolution [66,67,[76][77][78]. Because climate variables are often the most important predictors for SDMs of disease vectors, these data should be very detailed [36,66,67,76].…”
Section: Discussionmentioning
confidence: 99%